The climate warming effect of a fen peat meadow with fluctuating water table is reduced by young alder trees - V. Huth; M. Hoffmann; S. Bereswill; Y. Popova; D. Zak; J. Augustin (Mires and Peat, 2018)
Black alder (Alnus glutinosa (L.) Gaertn.) occurs naturally in temperate marshes and in minerotrophic peatlands and is also suitable for paludiculture - the cultivation of biomass on wet or rewetted peatland. We investigated the effect of a newly established black alder plantation on the greenhouse gas (GHG) balance of a degraded fen in north-eastern Germany over a two-year period (August 2010–August 2012). We compared the alder plantation (Awet) with an extensively used meadow (Mwet) and a drier reference meadow (Mmoist). GHG fluxes were measured monthly to bi-monthly using the closed chamber method. Our results show that Awet was a slight net GHG (in CO2-eq) sink of 3.4 ± 1.7 t ha-1 yr-1, Mwet was a moderate net GHG source of 9.6 ± 1.2 t ha 1 yr-1, and Mmoist was a strong net GHG source of 24.5 ± 1.6 t ha-1 yr-1. This was mainly driven by CO2 uptake at the two very moist (wet) sites and by high CO2 release at the drier reference site. Awet was a larger CO2 sink than Mwet, probably due to additional CO2 uptake by the alder stand at Awet and carbon export in plant material harvested from Mwet. All sites were significant CH4 sources. Substantial CH4 emission peaks were observed at all sites following extraordinarily heavy precipitation during the summer of 2011, which accounted for up to 70 % of the accumulated two-year CH4 emissions. However, the Awet site generally emitted less CH4, possibly due to the effective oxygen transport mechanism in black alders. N2O emissions were negligible at all three sites. Our results indicate that the GHG balances of formerly drained fens benefit in the short term from planting of black alders, mostly due to reduced CH4 emissions. This study highlights the importance of acknowledging extreme precipitation events and groundwater fluctuations for the derivation of reliable GHG emission factors.